Design of band‐rejected UWB planar antenna with integrated Bluetooth band. Issue 14 (1st November 2016) - Yadav, Swati; Gautam, Anil Kumar; Kanaujia, Binod Kumar; Rambabu, Karumudi
Abstract : In this study, a compact monopole antenna along with Bluetooth band and a band notched characteristic for ultra wideband (UWB) applications is designed. The antenna consists of a triangular shaped patch, an L‐shaped ground plane and a tapered microstrip feedline to obtain UWB operation. An additional resonance is excited for the Bluetooth band (2.4–2.48 GHz) by attaching an L‐shaped strip to the radiator. Further, a C‐shaped slit is etched in the radiator to restrict electromagnetic interference at IEEE INSAT/Super‐Extended C‐band from 6.7–7.1 GHz. The size of the antenna is only 13 × 24 × 1.6 mm 3 . A prototype of the proposed design is fabricated to validate the performance of the antenna. Measured results show that the antenna successfully operates over Bluetooth and entire UWB bands except the IEEE INSAT/Super‐Extended C‐band. A large bandwidth of 21.4 GHz from 3.1 to 24.5 GHz for UWB band is obtained. Current distribution on the antenna is used to develop design equations, and analysed the effect of L‐shaped strip and C‐shaped slit on the antenna operation. The simple structure and small size of the antenna makes it suitable for most of the wireless communication systems.